(untitled) (Perner’s Contacts, 2014)
The article deals with wheel suspension of formula student. A proposal follows the rules of SAE International. SAE International is an organizer of Formula Student/SAE competition. Races of formula student are organized all over the world. This competition is becoming very popular in Central Europe and VŠB - TU Ostrava would like to join this competition in the next year. This article was created during the development of the first generation of Formula Student at VŠB-TU Ostrava.